The Fading Attitude of Nationalism towards the Millennial Generation at Muhammadiyah University of Riau - Hudi, Ilham; Khairunnisa, Salsabila; Maharani, Ovalia Hermansyah; Putri, Popi Andika; Ramdani, Devinda; Ameliya, Ameliya; Jannah AD, Ghina Raudhatul (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This article discusses how nationalist attitudes influence the millennial generation in the context of Pancasila citizenship education. This education is the basis for increasing the nationalistic attitude of the millennial generation, which has an important role in building the country's future. In this article, we will discuss the introduction, research methodology used, results, and discussion regarding the decline in nationalist attitudes towards the millennial generation; a decline in nationalist attitudes towards the millennial generation; causes of the decline in the spirit of nationalism in the millennial generation; and a list of bibliography used in the derivation.